Celiac Disease Among Patients with Type 1 Diabetes Mellitus: Celiac Disease and Type 1 Diabetes Mellitus - Jaffar, Munfoosa; Qazi, Nayla; Saleem, Maleeha; Fatima, Misbah; Iqbal, Mehwish; Jabeen, Fatima (Pakistan Journal of Health Sciences, 2025)
The prevalence of celiac disease (CD) in type-1 diabetes mellitus (T1DM) may vary depending on the region, genetic background, and screening practices. Objectives: To determine the frequency of CD in patients with T1DM. Methods: This cross-sectional study was conducted at the Outpatient Department and Pediatric Ward of Children’s Hospital and Institute of Child Health, Multan, Pakistan, from February 2024 to July 2024. The inclusion criteria were children aged 2-18 years with type 1 diabetes mellitus (T1DM). Anti-transglutaminase assessment for the diagnosis of CD was performed, and it was deemed positive if the serum anti-tissue transglutaminase IgA antibody level was ≥100 IU/mL or the histopathology of the intestinal biopsy specimen was consistent with Marsh category 3 or higher. Data analysis was performed using IBM-SPSS Statistics, version 26.0. Results: The mean age was 9.03±3.6 years. There were 57 (58.2%) children who were male. Fifty-two (53.1%) children belonged to middle-class families. A positive family history of T1DM, autoimmune thyroiditis, and CD was noted in 46 (46.9%), 10 (10.2%), and 6 (6.1%) cases, respectively. The diagnosis of CD was confirmed in 20 (20.4%) children with T1DM. There were 4 (20.0%) and 2 (10.0%) patients with positive CD who had a positive family history of autoimmune thyroiditis and CD, respectively. Conclusions: The frequency of celiac disease was high among children with type 1 diabetes mellitus. The utility of anti-tTG evaluation is a non-invasive diagnostic tool for the screening of CD and can be utilized for the early diagnosis of CD in children with T1DM.